Franck–Condon simulation for unraveling vibronic origin in solvent enhanced absorption and fluorescence spectra of rubrene. Issue 20 (21st February 2017) - Hu, Ying; Wang, Chen-Wen; Zhu, Chaoyuan; Gu, Fenglong; Lin, Sheng-Hsien
Abstract : The damped FC method shows how and which local modes are responsible to solvent enhance vibronic spectra. Abstract : Quantum chemistry calculations at the level of (TD)-DFT plus PCM solvent models are employed for analyzing potential energy surfaces and as a result two local minima with D 2, two local minima with C 2H, and one second-order transition state with D 2H group symmetry are found in both ground S0 and excited-state S1 potential energy surfaces. Simulated vibronic coupling distributions indicate that only second-order transition states with D 2H group symmetry are responsible for observed absorption and fluorescence spectra of rubrene and vibrational normal-motions related with atoms on the aromatic backbone are active for vibronic spectra. The Stokes shift 1120 cm −1 (820 cm −1 ) and vibronic-band peak positions in both absorption and fluorescence spectra in non-polar benzene (polar cyclohexane) solvent are well reproduced within the conventional Franck–Condon simulation. By adding damped oscillator correction to Franck–Condon simulation, solvent enhanced vibronic-band intensities and shapes are well reproduced. Four (three) normal modes with vibration frequency around 1550 cm −1 (1350 cm −1 ) related to ring wagging plus CC stretching and CH bend motions on the backbone are actually interpreted for solvent enhanced absorption (fluorescence) spectra of rubrene in benzene and cyclohexane solutions.